Biology, Pathogenicity, and Genetic Diversity of the Rice Pathogen Ustilaginoidea virens in Heilongjiang Province, China - Peng Guo; Xiaofeng Xu; Yue Ma; Niaz Nihal; Mingxiu Yang; Zhe Ni; Younis Haseeb; Lei Hou; Anqi Lv; Junhua Zhang (Biology)
Rice false smut (RFS) is pervasive and has emerged as the primary disease affecting rice productivity. Due to the lack of effective chemical control, disease-resistant varieties are the primary method of managing the disease. This study aimed to investigate the influence of biological characteristics such as hyphal growth rate, spore production and germination ability on the pathogenicity of Ustilaginoidea virens. The genetic diversity of 86 U. virens isolates was analyzed, and the tolerant varieties were identified using Rep-PCR molecular markers. The results indicated that among the U. virens isolates analyzed, about 31, 27 and 28 strains exhibited fast, medium and slow mycelium growth rates, respectively. Among the U. virens isolates analyzed, about 33, 27 and 26 strains exhibited strong, medium and weak sporulation abilities, respectively. In addition, among the U. virens isolates analyzed, about 29, 30 and 27 strains exhibited strong, medium and weak spore germination, respectively. No significant correlation was noted between mycelium growth rate and pathogenicity, but sporulation ability, spore germination ability and liquid culture were positively correlated (p < 0.05). Moreover, the genetic structure of U. virens was diverse and complex. There was a significant correlation between the genetic differentiation and pathogenicity of U. virens in Heilongjiang Province, China, with a maximum coefficient of 0.1786 and a minimum coefficient of 0.0129 between Harbin and Suihua, but no significant correlation was found with gene groups or geographical regions. The study found that genes and geographical population variation were primarily within the population, with 95.63% and 4.37% variation (p > 0.05), respectively, while pathogenicity population variation was mainly within the population, with 86.08% and 13.92% variation (p > 0.05), respectively. Pathogenicity had a significant effect on the differentiation of U. virens. Most rice varieties were susceptible, with 3 resistant, 8 moderately resistant, 9 moderately susceptible, 8 susceptible and 12 highly susceptible to RFS disease. Collectively, these results indicate that the tolerance of rice against U. virens is poor, which merits further investigation.